Preferences of the Farmers towards Peri-Urban Agricultural Practices - Jagriti Rohit , S.K Dubey , Premlata Singh , B.K Singh and N V Kumbhare, (Indian Journal of Extension Education, 2018)
Crop production decisions reflect preferences of farmers which are based on the structure of incentives and constraints that characterize agricultural systems. Therefore, an assessment of the intensities of farmer preferences can provide useful guidance for the choice of appropriate strategies to improve productivity and incomes. The study was undertaken in Hapur district of Uttar Pradesh and Faridabad district of Haryana in order to understand the preferences of farmers towards various practices related to peri-urban agriculture and the reasons for taking up the same. Asample of 120 farmers, 30 each from four randomly selected villages from the above two districts was selected for the study. Data were collected using personal interview method utilizing semi-structured interview schedule and focused group discussion. The study revealed that 44.6 per cent farmers preferred private sector vegetable hybrid seeds as compared to recommended vegetable varieties of public sector institution and tube well was the most preferred source of irrigation. In case of financial decisions, short-term loan was preferred over other loans and farmers were willing to enter in contract farming. Assured market was the foremost reason for the farmers to practice peri-urban agriculture.